Study of the Matrix Shrinkage on a Polymer Matrix Composite under a Drop of Temperature - Le, Thi Tuyet Nhung; Trieu, Van Sinh; Vu, Dinh Quy (JST: Engineering And Technology For Sustainable Development, 2022)
A polymer composite material consists of two different phases with very different mechanical properties. Thus, there is a shrinkage when a decrease in temperature appears. This present paper focuses on the matrix shrinkage of a unidirectional polymer matrix composite under a temperature drop. A Rayleigh–Ritz method is used to rapidly determine the matrix displacement (matrix shrinkage) field of virgin samples (initial state, without thermo oxidation). Additionally, numerical simulations are also carried out. A comparison of maximum matrix shrinkages is carried out among the experiment measurement, the Rayleigh–Ritz method, and the numerical simulation method. The numerical results of the matrix displacement are compared to the experiment and the Rayleigh–Ritz method. There is a good correlation between the results obtained by the two methods. Then, an assessment of the reliability of numerical simulations is given. The numerical simulations are then used to analyze the evolution of stress along the different paths on the sample to predict the damage behavior.